Using dramatic role-play to develop emotional aptitude - Dinapoli, Russell (International Journal of English Studies, 2009)
As university educators, we need to prepare students for the transition from the information age to what Daniel H. Pink (2005) calls the conceptual age, which is governed by artistry, empathy and emotion, by including in the curricula activities that stimulate both hemispheres of the brain. This can be done by promoting activities that energize what Daniel Goleman (1995) refers to as emotional intelligence, and it further maintains that, as Paul Ekman (2003) suggests, the ability to detect feelings improves communication. Recognizing the need to include in the curricula procedures that help develop students’ right brain aptitudes and enhance their communication skills, I have endeavoured to introduce dramatic scene study as a sustained activity in my English for Specific Purposes courses at the Universidad de Valencia. My aim was to energize the students’ creative and emotional aptitudes, as well as to dynamize effective teamwork. This article sustains that dramatic role-play, based on scripted scene study and related improvisational activities, is one way of achieving this.